Locally sparse and robust partial least squares in scalar-on-function regression - BEYAZTAŞ, UFUK (My University, 2024)
AbstractWe present a novel approach for estimating a scalar-on-function regression model, leveraging a functional partial least squares methodology. Our proposed method involves computing the functional partial least squares components through sparse partial robust M regression, facilitating robust and locally sparse estimations of the regression coefficient function. This strategy delivers a robust decomposition for the functional predictor and regression coefficient functions. After the decomposition, model parameters are estimated using a weighted loss function, incorporating robustness through iterative reweighting of the partial least squares components. The robust decomposition feature of our proposed method enables the robust estimation of model parameters in the scalar-on-function regression model, ensuring reliable predictions in the presence of outliers and leverage points. Moreover, it accurately identifies zero and nonzero sub-regions where the slope function is estimated, even in the presence of outliers and leverage points. We assess our proposed method’s estimation and predictive performance through a series of Monte Carlo experiments and an empirical dataset—that is, data collected in relation to oriented strand board. Compared to existing methods our proposed method performs favorably. Notably, our robust procedure exhibits superior performance in the presence of outliers while maintaining competitiveness in their absence. Our method has been implemented in the package in
Keywords: İstatistik; Temel Bilimler; Statistics; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; Psikoloji; ÇOK DİSİPLİNLİ BİLİMLER; PSİKOLOJİ, MATEMATİKSEL; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; PSYCHOLOGY; MULTIDISCIPLINARY SCIENCES; PSYCHOLOGY, MATHEMATICAL; Multidisipliner; Multidisciplinary; Dimension reduction; Functional linear regression; Robustness; Sparse estimation